Will the security architecture of the western Pacific change post-COVID 19?. (2nd January 2020) - Banerjee, Somen
ABSTRACT: The Indo-Pacific, combines a panoply of regions and blends multiple security architectures. Some regions are dominated by non-traditional security threats, while others are unstable and rife with security dilemma. Instability and disorder are most palpable in the maritime domain, especially in the geographical region of the western Pacific. From the beginning of 2020, China has intensified its assertiveness in the South China Sea, including the announcement of two administrative districts and transgressions by its survey ship Haiyang Dizhi 8. Some attribute these developments to the COVID-19 outbreak. Enhanced US posture in the region seems to have little effect on Chinese revanchism. This article assesses the spurt of developments in the South China Sea during the COVID-19 pandemic. It establishes the conceptual framework for analysing the change in the regional order. It evaluates the regional security architecture of the western Pacific and the efficacy of the putative order. The prospective change in the security order of the western Pacific and response is also examined.